Pregnancy losses in Bos indicus-influenced beef and dairy recipients assigned to a fixed-time embryo transfer protocol - Munhoz, S. K. [UNESP] (2024)
Pregnancy losses from fixed-time embryo transfer (FTET) to calving were evaluated in Bos indicus-influenced beef and dairy recipients. Data from 4366 FTET events were collected from Nelore × Angus recipient heifers, and from 38538 FTET events in Gir × Holstein recipient heifers and cows. In beef recipients, pregnancy losses were greater (P < 0.01) from FTET (day 7 of the experiment) to day 32 compared with day 32–100 and with day 100 to calving (58.7, 39.5, and 36.7%, respectively), and did not differ (P = 0.56) between these latter periods. Recipients that lost the pregnancy from FTET to day 32 gained less (P < 0.01) body condition score after FTET compared with recipients that maintained the pregnancy. Pregnancy losses from day 32 to calving were greater (P < 0.01) in recipients reared in drylots and moved to pastures on day 32 compared with recipients reared on pasture. In dairy recipients, pregnancy losses from FTET (day 7) to day 32 were greater (P < 0.01) than losses from day 32 to calving (50.4 and 29.4%). Pregnancy losses throughout gestation were greater (P < 0.01) when the FTET event was performed during the warm season, and greater (P < 0.01) in recipients with < 3/8 Gir influence. Recipients with ≥ 3/8 Gir influence experienced a lesser (P ≤ 0.05) increase in pregnancy losses during the warm season compared with recipients with < 3/8 Gir influence. Collectively, this experiment provides novel information about pregnancy losses in B. indicus-influenced herds receiving FTET.